LAYOUT ANALYSIS OF V-GROOVE SOLAR COLLECTOR (Nigerian Journal of Technology, 2024)
This study undertakes the comparative layout study of a V-grooved solar air heater (SAH) with a view to show the optimum design layout for the air heater. Several studies have been conducted on comparing isolated V-groove SAH with other designs of SAH. However, from literature there have not been studies on the comparative layout pattern of V-groove SAHs. It was equally, observed from literature that design layouts of V-groove systems are mainly parallel in nature. Thus, there is a knowledge gap on studies focusing on the layout pattern of V-grooved systems. Thus, the paper seeks to address this with the research question as “What is the optimum layout for a V-groove solar air heater?” In comparison to active mode of solar air heating, the heat energy analysis of passive solar air heaters, has not been widely studied. Hence, the study is limited to natural convection systems. The study focuses on comparative analysis/evaluation of two basic layout of V-grooved solar air heater- parallel and perpendicular air flow design layouts. The outcome of the work has revealed that the systems can easily be adapted to low temperature applications. From the study, it is deduced that even though the Parallel designed layout of V-groove SAH showed a better efficiency when compared to the Perpendicular designed layout of V-groove SAH that both of them are statistically the same at 5% probanility level using the completely randomized design (CRD) statistical method. The layout pattern does not necessarily mean better output in operation. However when compared to similar works done using the same dimensions for flat plate designs that there is an appreciable improvement in the efficiency of operation.